Gas Fermentation Expands the Scope of a Process Network for Material Conversion. Issue 11 (28th September 2020) - Geinitz, Bertram; Hüser, Aline; Mann, Marcel; Büchs, Jochen
Abstract: Biotechnological fermentation is a well‐established process, however, it is far from being fully understood and exploited. A new area of fermentation technology that has evolved over the recent decades is gas fermentation. Many microorganisms have been reported in literature to be capable of utilizing a variety of gases such as CO, CO2, H2, and CH4 under anaerobic or aerobic conditions as their main carbon and/or energy source. Mostly waste stream gases from industrial plants or those that can be produced via the gasification of solids are investigated. This review focuses on the currently available scientific knowledge about gas fermentation processes, particularly anaerobic syngas fermentation and aerobic methane fermentation. Gas fermentation processes are compared with aerobic and anaerobic fermentation processes based on dissolved solid substrates. Also, the potential of gas fermentation when integrated into a biotechnological network of processes is outlined. Abstract : This review highlights the advantages of integrating gas fermentation into a network of material conversion processes. In addition, the challenges of using gaseous substrates compared to standard liquid fermentation processes are discussed and the relevant reviews of gas fermentation are summarized.